Is there a homogenous entrepreneurial mindset? Reflections based on a complex value-theoretical approach - Grünhut, Zoltán; Bodor, Ákos; Komlósi, Éva; Schepp, Zoltán (Vezetéstudomány / Budapest Management Review, 2024)
This paper falls within the scope of entrepreneurship research focused on entrepreneurs as agents with individual personality traits. This paper first overviews the relevant literature – both early and current theories – of this research agenda. The main conceptual findings are then linked to the value theoretical framework developed by Shalom H. Schwartz, which seems to reflect, with limitations, on the basic content of these framings about entrepreneurial traits. Based on the Schwartzian background, this paper sheds light on the linkages among the individual value structures and specific personality traits considered important for entrepreneurial actors. The empirical portion used data from the European Social Survey to identify four distinct entrepreneurial mindsets among European entrepreneurs.